Exploring The Determinants of Sustainable Interest To Use E-Wallet: The Mediating Role of Customer Satisfaction - Masaalah Marasabessy; Achmad Sani Supriyanto; Vivin Maharani Ekowati; Setiani Setiani; Siswanto Siswanto; Ahmad Tibrizi Soni Wicaksono; Kurniawati Meylianingrum; Titis Miranti; Forbis Ahamed (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The current rapid development of the times has created the birth of the evolution of payment instruments such as e-wallets. The evolution of this means of payment facilitates human activities in terms of transactions. The ease, convenience, speed, and benefits offered by Payment System Service Providers (PJSP) such as e-wallets can attract people's interest in adopting this system. Purpose: This study examines the direct effects of perceived ease of use, perceived usefulness, and e-service quality on sustained e-wallet use in Jayapura City, with customer satisfaction as a mediator. Design/methodology/approach: The research method adopted is quantitative, with an explanatory approach. The population in this study was the residents of Jayapura City, and the sampling technique was purposive, resulting in a sample size of 200 respondents. Data were collected via a questionnaire and then evaluated using SmartPLS v.4.1.0.6. Findings/Result: The findings show that perceived convenience does not affect long-term interest in using e-wallets. Meanwhile, perceived benefits, e-service quality, and customer satisfaction favourably and significantly impact sustained e-wallet usage. These findings also demonstrate that customer satisfaction can mediate the relationship between perceived convenience, perceived benefits, and e-service quality regarding Jayapura City residents' sustained interest in utilizing e-wallets. Conclusion: This study shows that the e-wallet payment system service provider can improve the services provided, increase the literacy of the people of Jayapura City regarding the operation of e-wallets and the urgency of using technology so that the people of Jayapura City are technology literate. In addition, the e-wallet should also be able to provide various promos that can attract the interest of the people of Jayapura City. Originality/Value (State of The Art): The findings of this research are intended as evaluation material and a basis for decision-making by e-wallet applications regarding interest in adopting e-wallets. Keywords: perceived benefits, e-service quality, customer satisfaction, sustainable interest, e-wallet